Reconfiguring Electoral Design Post-Constitutional Court Decision No. 135/PUU-XXII/2024: Prospects for Meaningful Voter Participation: Rekonfigurasi Desain Pemilu Pasca Putusan Mahkamah Konstitusi Nomor 135/PUU-XXII/2024: Prospek Partisipasi Pemilih Bermakna - Sani, Arsul; Darmawan, Devi; Noor, Firman; Romli, Lili (Jurnal Konstitusi, 2025)
The Constitutional Court Decision No. 135/PUU-XXII/2024 regarding the separation of national and regional elections marks a fundamental reconfiguration of Indonesia’s electoral design. This empirical legal study analyzes the logic of electoral timing changes and their implications for the quality of participation amidst the paradox of low public deliberation. Based on secondary data and Focus Group Discussions (FGD) by the BRIN Political Research Center, this study finds that separating electoral cycles serves as an institutional intervention to reduce cognitive overload and create reflective space for voters. The study concludes that this transformative effect is conditional: meaningful participation can only be realized through meaningful competition. This requires the establishment of three main pillars: internal political party democratization, independence of election organizers, and regulations ensuring legal certainty.